डोंगर वारली-मराठी-2 - Nadge, N.B.; Guraw, S.J.; Ranganatha, M.R.; Vad, K.G.; Rajyashree, K.S. (Central Institute of Indian Languages Mysore, 1985)
Dungar Varli Marathi-2 is a primer for class-2. The book is intended for Varli students, to learn Marathi language through their dialect.
Dungar Varli Marathi-2
Keywords: Marathi; Primer; Marathi; Marathi